Propuesta de mejora del clima Organizacional en MTZ Ltda. Villavicencio, Meta. (2022)
The present work was developed to make a diagnosis of the organizational climate that exists at the moment in the company MTZ Ltda, for this a descriptive study was applied, since this allows to determine the real situation of the organizational climate, where possible actions were identified to make an improvement and/or strengthen the existing work climate in the organization; For this purpose, the instrument for Measuring Climate in Colombian Organizations, called (IMCOC), was used as a tool for collecting information with the employees, which through 45 questions in a survey design allowed to identify the characteristics, forms of behavior, peer perceptions and attitudes of the studied population. That is to say, the questions were classified in the variables that according to this method compose the organizational climate such as: Objectives, Cooperation, Leadership, Decision Making, Interpersonal Relations, Motivation and Control, which can directly or indirectly influence the productivity of the organization. With the realization of this work it is possible to improve aspects or variables that at a certain moment have not been considered by the managers and workers as influencing the organizational climate; so it becomes for the company an opportunity for improvement by proposing strategies that allow to intervene, thus improving the work environment, in favor of providing a better service to its customers.